The Release of Organic Acids and Low Molecular Weight Carbohydrates from Matcha Tea After In Vitro Digestion - Nekvapil, Jiří; Sumczynski, Daniela; Salek, Richardos Nikolaos; Bučková, Martina (Nutrients, 2024)
BACKGROUND/OBJECTIVES: This study tested the influence of in vitro digestion on the release of organic acids and low molecular weight saccharides of matcha. METHODS: The concentrations of analytes in the raw and undigested portion of matcha were measured using HPLC with spectrometric and refractometric detection to establish their residual values after a two-step enzymatic digestion that was finally presented as a retention factor. RESULTS: It was established that dry matter digestibility values after simulated gastric and both gastric and intestinal phases were 67.3 and 85.9%, respectively. Native matcha, citric acid (44.8 mg/g), malic acid (32.2 mg/g), trehalose (36.1 mg/g), and L-arabinose (8.20 mg/g) reached the highest values and were predominant, whereas D-fructose, xylose, maltose, and saccharose were not detected. Regarding gastric phase digestion, succinic and malic acids, trehalose and D-glucose were the worst-releasing compounds and their remaining factors reached 34, 19, 18, and 50%, respectively, whereas L-arabinose was completely released. Focusing on gastric and small intestinal digestion, the least-releasing compounds of matcha tea leaves were succinic acid and trehalose, with their retention factors at 7 and 13%, which can proceed with the leaf matrix to the large intestine. CONCLUSIONS: Malic, oxalic, and citric acids, the carbohydrates D-glucose, L-arabinose, and L-rhamnose, are almost entirely released from matcha tea during digestion in the stomach and small intestine and can be available for absorption in the small intestine. In the measurement of oxalic acid, considering that the process of shading tea leaves increases the concentration of this acid and its retention factor value is too small, it would be appropriate in the future to evaluate the recommended maximum daily intake of matcha tea for people sensitive to the formation of urinal stones.
Keywords: Citric Acid; sacharidy; maláty; listy rostlin; Digestion; Malates; Tea; green tea; Plant Leaves; Carbohydrates; low molecular weight carbohydrate; foods; kyselina citronová; matcha; molekulová hmotnost; in vitro digestion; bioactive compound; organic acid; trávení; Camellia sinensis; Molecular Weight; čaj